The complete nucleotide sequence of a rice 17S rRNA gene. - Takaiwa, F (1984)
The complete nucleotide sequence of a rice nuclear 17S rRNA gene (rDNA) has been determined. The rice rDNA is 1812 bp long and its G + C content is 51.3%. This nucleotide sequence shows 79%, 80% and 80% homology to those of yeast, Xenopus laevis and rat 18S rDNAs, respectively. Divergency of nucleotide sequences is largely attributed to five blocks of highly variable regions, where eukaryotic specific sequences can be observed.